Childhood ADHD is Strongly Associated with a Broad Range of Psychiatric Disorders during Adolescence: a Population-Based Birth Cohort Study - Yoshimasu, Kouichi (2012)
BACKGROUND: To evaluate associations between ADHD and comorbid psychiatric disorders using research-identified incident cases of ADHD and population-based controls. METHODS: Subjects included a birth cohort of all children born 1976–1982 remaining in Rochester, MN after age five (n = 5718). Among them we identified 379 ADHD incident cases and 758 age-sex matched non-ADHD controls, passively followed to age 19 years. All psychiatric diagnoses were identified and abstracted, but only those confirmed by qualified medical professionals were included in the analysis. For each psychiatric disorder, cumulative incidence rates for subjects with and without ADHD were estimated using the Kaplan-Meier method. Corresponding hazard ratios (HR) were estimated using Cox models adjusted for gender and mother’s age and education at the subject’s birth. The association between ADHD and the likelihood of having an internalizing or externalizing disorder was summarized by estimating odds ratios (OR). RESULTS: ADHD was associated with a significantly increased risk of adjustment disorders (HR=3.88), conduct/oppositional defiant disorder (HR=9.54), mood disorders (HR=3.67), anxiety disorders (HR=2.94), tic disorders (HR=6.53), eating disorders (HR=5.68), personality disorders (HR=5.80), and substance-related disorders (HR=4.03). When psychiatric comorbidities were classified on the internalization-externalization dimension, ADHD was strongly associated with coexisting internalizing/externalizing (OR=10.6), or externalizing-only (OR=10.0) disorders. CONCLUSION: This population-based study confirms that children with ADHD are at significantly increased risk for a wide range of psychiatric disorders. Besides treating the ADHD, clinicians should identify and provide appropriate treatment for psychiatric comorbidities.